Model of Accounting Information System and SMEs Performance in Contingency Theory Perspective - Nur Diana; Sudarmiatin Sudarmiatin; Agus Hermawan (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The global industry has been affected by the COVID-19 pandemic, particularly small and medium-sized businesses, which has a negative effect on organizational performance, planning, control, and systems. This causes small and medium-sized businesses to take certain actions relating to the use of accounting information systems for their own benefit, which can impact the performance of SMEs that are influenced by environmental and organizational factors. This study seeks empirical evidence of the effect of accounting knowledge, business experience, and business strategy on the performance of small and medium-sized enterprises (SMEs) as mediated by accounting information systems. Utilizing primary data sources, survey data collection techniques, and research samples comprised of SME owners and managers, an explanatory causality approach is utilized. Using a simple random sampling technique, individual units of analysis, a one-shot study time horizon, and path analysis, the data were evaluated. In addition, the results demonstrated that accounting expertise and business experience positively affect accounting information systems. This study also revealed a positive relationship between accounting knowledge and SME performance. SME performance is negatively affected by business experience. In addition, the accounting information system as mediator demonstrates that SME performance increases as a result of business experience.